Tai Chi: Exercise for Increasing Muscle Flexibility in the Elderly - Rakphongsiri, Kessara (Journal of Health Science of Thailand, 2017)
When the age increased, the degenerate changes will occur in all systems with including musculoskeletal system. These change affect the decrease in muscle flexibility. Many studies support that exercise can increase muscle flexibility. This exercise should be a slow movement of several other common joints and muscles together with stretching. Past studies found that the trend fo muscle flexibility in the elderly was reduced with age. However, exercise regularly with Tai Chi for a long time continously can increase muscle flexibility in the elderly. It may be concluded that Tai Chi is the exercise proper for increasing the flexibility of muscle in the elderly.